Enhancing profitability of nomadic Gaddi goat production system for augmenting farmer’s income - NARENDER KUMAR, P.K. DOGRA1, VARUN SANKHYAN ANJALI KUMARI, ANKAJ THAKUR (Indian Journal of Animal Production and Management, 2020)
Gaddi is a distinct tribe of nomadic pastoralists of Himachal Pradesh involved in rearing of sheep and goatsof Gaddi breed. Their flocks are managed totally under extensive (migratory) production system. Duringsummers the flocks climb to high altitude alpine Himalayan pastures and during winters they are grazedin the foot hills. The present study was conducted on Gaddi goats maintained by the Gaddi shepherdsunder AICRP on Goat Improvement (2010-17). The animals were provided strategic breeding, feeding andhealth inputs under field conditions and periodic data recordings were done. The overall net income fromthe sale of surplus and culled animals ranged between Rs. 5.2 to 13.04 lac per annum. The net incomeper animal per year was observed in the range of Rs. 743.93 and 1120.74. The percent change in overallnet income and net income per animal per year recorded during the period (2010-17) was to the tune of129.42 and 43.24 percent, respectively. This study has demonstrated that nomadic goat farming can bemade a profitable and economically viable enterprise by providing critical inputs to overcome the existingconstraints